Complex multimorbidity and health outcomes in older adult cancer survivorsa. Issue 2 (1st July 2017) - Warner, David F.; Schiltz, Nicholas K.; Stange, Kurt C.; Given, Charles W.; Owusu, Cynthia; Berger, Nathan A.; Koroukian, Siran M.
Abstract : Objective: To characterize complex multimorbidity among cancer survivors and evaluate the association between cancer survivorship, time since cancer diagnosis, and self-reported fair/poor health, self-rated worse health in 2 years, and 2-year mortality. Methods: We used the 2010–2012 Health and Retirement Study. Cancer survivors were individuals who reported a (nonskin) cancer diagnosis 2 years or more before the interview. We defined complex multimorbidity as the co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes. In addition to descriptive analyses, we used logistic regression to evaluate the independent association between cancer survivor status and health outcomes. We also examined whether cancer survivorship differed by the number of years since diagnosis. Results: Among 15, 808 older adults (age ≥50 years), 11.8% were cancer survivors. Compared with cancer-free individuals, a greater percentage of cancer survivors had complex multimorbidity: co-occurring chronic conditions, functional limitations, and geriatric syndromes. Cancer survivorship was significantly associated with self-reported fair/poor health, self-rated worse health in 2 years, and 2-year mortality. These effects declined with the number of years since diagnosis for fair/poor health and mortality but not for self-rated worse health. Conclusion: Cancer survivor status is independently associated with more complex multimorbidity, and with worse health outcomes. These effects attenuate with time, except for patient perception of being in worse health.